Test–retest reliability of the Kuopio instrument for fathers (KIF): a questionnaire to assess fathers’ feelings, experiences and preparation for their wife/partner's delivery - Sapountzi-Krepia, Despina; Raftopoulos, Vasilios (My University, 2007)
To assess the test–retest reliability of the Greek version of the Kuopio Instrument for to assess the test–retest reliability of the Greek version of the Kuopio Instrument for Fathers (KIF) questionnaire that explores fathers’ feelings, experiences and preparation for their wife/partner's delivery.
Keywords: Fathers; Maternity services; Delivery; Labour; Kuopio Instrument for Fathers; Test–retest reliability